Microfluidic Devices for Electrical Interrogation of Gap Junction Connectivity - Dungan, Joel. (Tufts University. Tisch Library., 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Electrical Engineering.; Advisor: Valencia Koomson.; Committee: Michael Levin, Sameer Sonkusale, and Jeffrey Borenstein.; Keywords: Electrical engineering, Developmental biology, and Engineering.